Breeding for Multipurpose Sugarcane: Evaluating Agronomic and Cell-Wall Traits for Sugar, Biomass, and Second-Generation Ethanol Production - Garcia, José María (2026)
Sugarcane (Saccharum spp.) is a highly efficient energy crop with increasing importance in both first- and second-generation (2G) ethanol production. Usage of sugarcane lignocellulosic residues for 2G ethanol provides a low-carbon alternative to fossil fuels and offers economic advantages by increasing ethanol output without expanding cultivated areas. As traditional breeding has primarily focused on sugar yield, there is a growing need for research aimed at developing multipurpose varieties that combine enhanced sugar and biomass yield with improved biomass digestibility for 2G ethanol production. In this study, early-stage sugarcane breeding populations were evaluated under field conditions using an integrated breeding approach encompassing key agronomic and cell-wall traits, including saccharification potential. Using mixed linear models, genetic parameters, correlations, and best linear unbiased predictors (BLUPs) were estimated to identify superior genotypes for multipurpose applications. Results revealed high breeding potential for stalk-related and biomass traits, particularly fibre yield, while low broad-sense heritability and genetic variability may limit selection for cell-wall traits. Strong negative genetic correlations (rg = −0.62 to −0.80) were found between stalk diameter and fibre content, while saccharification potential showed only a weak negative correlation with lignin content (rg = −0.26) suggesting that additional recalcitrant factors may influence cell-wall digestibility. BLUPs-based ranking enabled the selection of promising multipurpose genotypes combining high sugar and biomass yield with improved cell-wall composition for 2G ethanol production. These findings provide new insights into the development of multipurpose sugarcane varieties and support integrated breeding strategies to optimize both sugar production and bioenergy applications.